Imaging and Patient Selection for Transcatheter Tricuspid Valve Interventions - Winkel, Mirjam G.; Brugger, Nicolas; Khalique, Omar K.; Gräni, Christoph; Huber, Adrian; Pilgrim, Thomas; Billinger, Michael; Windecker, Stephan; Hahn, Rebecca T.; Praz, Fabien (Frontiers in Cardiovascular Medicine, 2020)
With the emergence of transcatheter solutions for the treatment of tricuspid regurgitation (TR) increased attention has been directed to the once neglected tricuspid valve (TV) complex. Recent studies have highlighted new aspects of valve anatomy and TR etiology. The assessment of valve morphology along with quantification of regurgitation severity and RV function pose several challenges to cardiac imagers assessing TR severity and guiding transcatheter valve procedures. This review article aims to give an overview over the role of modern imaging modalities during assessment and treatment of the TV.